A Novel Error-Injected Solution for Compensation of Current Measurement Errors in PMSM Drive - Zhang, Qiaofen; Guo, Haohao; Liu, Yancheng; Guo, Chen; Zhang, Fengkui; Zhang, Zhenrui; Li, Guanhua (IEEE transactions on industrial electronics (1982), 2023)
Current measurement errors including offset error and scaling error can generate asymmetric phase currents and first- and second-order harmonics in motor steady-state torque/speed. In this article, a novel method using artificial error injection is proposed to calculate and compensate for the offset error and scaling error in permanent magnet synchronous motor drive. The artificial errors are injected to introduce additional equations for the calculation of current measurement errors because of the problem of rank deficiency existing in the equation about the offset/scaling error and the first/second-order harmonic magnitude. In order to guarantee the calculation accuracy of the offset error and scaling error, the cascade multiple second-order generalized integrators (cascade-multi-SOGIs) are employed to extract the magnitudes of the first- and second-order harmonics in steady-state speed error under different error injections. The method does not require the values of motor parameters, and it can be used either as part of an initial debugging or start-up program, or periodically during the regular operation of the motor. The experiments can verify its validity and practicability.